'A country can only have a foreign policy it can afford': South Africa's Economic Reaction to Zimbabwe's Independence, 1980–1982. Issue 3 (14th September 2022) - Nkomo, Lotti
Abstract : The largely cordial relationship between Rhodesia (now Zimbabwe) and South Africa, established in the 1890s, instantly turned hostile at Zimbabwe's independence in 1980. This reconfiguration, marked by Harare's termination of diplomatic contact with Pretoria, was due to divergent ideologies between apartheid South Africa and the black majoritarian Zimbabwean government. Shying away from the orthodox approach that emphasises the security and military dimension of the breakdown of relations, the article utilises the lens of diplomacy and everyday interstate engagements to explore Zimbabwe's anti-apartheid posture and its campaign against South Africa's occupation of Namibia. It considers how South Africa attempted to exploit Zimbabwe's overwhelming economic reliance on its trade and transportation networks and infrastructure to assert its power and force its northern neighbour to abandon its hostile stance. Relying largely on recently available archival material, I argue that Zimbabwe terminated political contact in order to force South Africa to change its domestic and regional politics while Pretoria adopted trade and transportation diplomacy as a stick with which to beat its obstinate neighbour.